Adaptation in Instruction for the Visually Impaired Students in Inclusive Setting - Javed, Najeeba; Swaira, Almas; Akmal, Farhana (Annals of Human and Social Sciences, 2025)
This study aimed to identify instructional adaptations for students with visual impairments in inclusive settings, specifically examining differences based on teachers age groups in Lahore and Vehari. Inclusive education requires effective instructional strategies for visually impaired students. However, many teachers lack the necessary training and resources, hindering the implementation of suitable adaptations. A quantitative research design was used. The sample consisted of 160 teachers from inclusive schools in Lahore and Vehari, selected through non-probability sampling. Data were collected using a self-developed checklist. An independent sample t-test was applied to analyze differences in instructional adaptation based on teachers age. Instructional adaptation was the core variable under investigation. The findings indicated no significant difference in instructional adaptations based on age groups. A major issue identified was insufficient training, which affected teachers capacity to address the needs of visually impaired students. It is recommended to organize regular teacher training programs, provide necessary teaching aids, and ensure appropriate facilities for effective inclusive education.